The prognostic analysis of further axillary dissection in breast cancer with 1-2 positive sentinel lymph nodes undergoing mastectomy - Zhao, Xueyi; Yang, Liu; Cao, Congbo; Song, Zhenchuan (Frontiers in Oncology, 2024)
Background:The ACOSOG Z0011 trial revealed that axillary lymph node dissection (ALND) may not be necessary in patients with 1-2 positive sentinel lymph nodes (SLNs) who undergo breastconserving surgery combined with postoperative radiotherapy. However, there remains controversy regarding the applicability of this approach in mastectomy patients. This study aims to analyze the prognostic differences and survival risk factors of whether to undergo ALND in patients with 1-2 SLNs breast cancer who have undergone mastectomy.Methods:A retrospective analysis was performed on cT1-2N0 breast cancer patients who received treatment at The Fourth Hospital of Hebei Medical University from January 2016 to December 2021, and patients were divided into two cohorts according to whether ALND was performed after sentinel lymph node biopsy (SLNB): the SLNB cohort and the SLNB+ALND cohort. The outcomes were locoregional recurrence rate (LRR), disease-free survival (DFS), and overall survival (OS). Propensity score matching (PSM) was performed balance patient characteristics. The Kaplan-Meier was used to plot survival curves. Cox proportional hazard models were used to identify independent risk factors associated with survival.Results:There were 812 patients with cT1-2 breast cancer and 1-2 SLN metastases were enrolled. After PSM, 234 patients with ALND and 234 without ALND were matched. After a median followup of 56.72 ± 20.29 months, the DFS and OS of the SLNB+ALND cohort showed no statistically significant difference from the SLNB cohort (p = 0.208 and p = 0.102, respectively), except for patients under 40 years old, SLNB+ALND group showed a reduction in LRR compared to SLNB group (11.1% vs. 2.12%, P= 0.044). Multivariate Cox analysis showed that younger (≤40 years), progesterone receptor(PR)-negative, and SLNB alone were independent risk factors for LRR; perineural invasion was a risk factor, while endocrinotherapy was a protective factor for DFS and OS in hormone receptor-positive breast cancer patients.Conclusion:ALND does not impact DFS and OS in breast cancer patients with 1-2 positive SLNs treated with mastectomy. Being younger (≤40 years), having a negative PR, and undergoing SLNB alone were independent risk factors for LRR. Given this finding, we recommend avoiding axillary treatment such as ALND or radiotherapy in patients without risk factors.